Electronic cigarettes: what are they and what do they do?. Issue 1 (15th January 2016) - Breland, Alison; Soule, Eric; Lopez, Alexa; Ramôa, Carolina; El‐Hellani, Ahmad; Eissenberg, Thomas
Abstract : Electronic cigarettes (ECIGs) use electricity to power a heating element that aerosolizes a liquid containing solvents, flavorants, and the dependence‐producing drug nicotine for user inhalation. ECIGs have evolved rapidly in the past 8 years, and the changes in product design and liquid constituents affect the resulting toxicant yield in the aerosol and delivery to the user. This rapid evolution has been accompanied by dramatic increases in ECIG use prevalence in many countries among adults and, especially, adolescents in the United States. The increased prevalence of ECIGs that deliver nicotine and other toxicants to users' lungs drives a rapidly growing research effort. This review highlights the most recent information regarding the design of ECIGs and their liquid and aerosol constituents, the epidemiology of ECIG use among adolescents and adults (including correlates of ECIG use), and preclinical and clinical research regarding ECIG effects. The current literature suggests a strong rationale for an empirical regulatory approach toward ECIGs that balances any potential ECIG‐mediated decreases in health risks for smokers who use them as substitutes for tobacco cigarettes against any increased risks for nonsmokers who may be attracted to them.